2017
DOI: 10.1089/chi.2016.0177
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enhancing School-Based Body Mass Index Screening Reports with Parent Education on Report Utility and Parental Intent To Modify Obesity Risk Factors

Abstract: Parental education can enhance the utility of the SBMIS report and parental intention to modify at least one obesity risk factor. SBMIS reports prompted parents of children with overweight and obesity to seek clinical care and limit sugar-sweetened drinks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…First, because of the design of the cross-sectional survey project, which collected all of the data at a single time point, there was a limit to the inference of the causation between the chemical exposures and obesity. Second, we used the education level of the individuals themselves instead of their parents' education level, which can be a factor, since parental education can change their intention to alter the obesity risk factor [38]. Third, chemical concentrations below the limit of detection were simply replaced by the value of the limit of detection divided by the square root of 2, which may cause inaccurate results.…”
Section: Discussionmentioning
confidence: 99%
“…First, because of the design of the cross-sectional survey project, which collected all of the data at a single time point, there was a limit to the inference of the causation between the chemical exposures and obesity. Second, we used the education level of the individuals themselves instead of their parents' education level, which can be a factor, since parental education can change their intention to alter the obesity risk factor [38]. Third, chemical concentrations below the limit of detection were simply replaced by the value of the limit of detection divided by the square root of 2, which may cause inaccurate results.…”
Section: Discussionmentioning
confidence: 99%
“…Both FNPA and Healthy Kids risk assessments offer potential value to clinicians to involve parents in selfassessing risk using validated tools. This study did not evaluate parent experience or behaviour change following FNPA risk assessment; however, promising results have been observed in earlier studies (15,16). Enhancing BMI screening with FNPA risk assessment at routine WCVs was beneficial for children aged 2-9 and 2-5 overall, specifically those with normal weight at baseline, compared with children whose parents did not complete FNPA at baseline.…”
Section: Discussionmentioning
confidence: 82%
“…Both FNPA and Healthy Kids risk assessments offer potential value to clinicians to involve parents in self‐assessing risk using validated tools. This study did not evaluate parent experience or behaviour change following FNPA risk assessment; however, promising results have been observed in earlier studies .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Evidence has shown that clinicians who are educated about care guidelines for overweight children were more likely to report using sources such as AAP News and other journals for latest evidence on the prevention and counseling of children who are overweight (Klein et al, 2010). Furthermore, Bailey-Davis, Peyer, Fang, Kim, and Welk (2017) found that parents who received this education on home environmental strategies were more likely to engage in modifying childhood obesity risk factors. Ihmels et al (2009) developed the Family Nutrition and Physical Activity (FNPA) tool designed to screen for family environmental factors that place a child at risk of becoming overweight.…”
Section: Introductionmentioning
confidence: 99%